THE CHEMICAL COMPOSITION OF ENAMEL OF TEETH WITH PRECERVICAL CARIES - S. P. Yarova; I. I. Zabolotnaya; E. S. Genzytskaya (Український стоматологічний альманах)
Form of cervical caries occurs in 20-30% of cases. Resistance to decay related to the structure and properties of dental tissues. The aim - to determine the mineral content of tooth enamel caries cervical depending on the depth of cracks and anatomical region. Research materials and their teeth were grinding on which diagnosed type cracks. We used raster (scanning) electron microscope JSM-6490 LV. In the chemical composition of enamel all the above areas identified statistically significant differences in Na containing is depending on the depth of cracks (p <0,05). Its concentration in the cutting edge (hill) was higher in the teeth of microcracks type I than type II and III, respectively, 2,4 ± 0,2 and 1,3 ± 0,2razy.Na equator and cervical area the largest amount of sodium was determined in tooth enamel microcracks of type III, in the equator - in 1,3 ± 0,1 and 2,1 ± 0,2razy; in the cervical area - in 1,1 ± 0,1 and 2,0 ± 0,4r\ times compared with samples with cracks of types I and II, respectively, p <0,05. In cervical enamel surface area and coronal caries pathology identified statistically significant differences in Na and Al containing and depending on the depth of cracks, p <0,05. In both areas the largest concentration of Na was determined in the teeth of the third type of enamel cracks and the least - of type II (p<0.05). In the cervical region and type of samples with aluminum Bulova 8,0 ± 3,0 times more than in the same section samples of types II and III, p <0.001. In the coronal enamel surface of the teeth it was to 8,5 ± 4,0 times more than the second and third types, p = 0.020. The data should be used to develop a set of therapeutic and preventive measures.